Precompact Sets, Boundedness, and Compactness of Commutators for Singular Integrals in Variable Morrey Spaces. (20th July 2017) - Wang, Wei; Xu, Jingshi
Abstract : We give sufficient conditions for subsets to be precompact sets in variable Morrey spaces. Then we obtain the boundedness of the commutator generated by a singular integral operator and a BMO function on the variable Morrey spaces. Finally, we discuss the compactness of the commutator generated by a singular integral operator and a BMO function on the variable Morrey spaces.